Trisomy 22 and intersex. Issue 1 (July 1994) - Nicholl, R M; Grimsley, L; Butler, L; Palmer, R W; Rees, H C; Savage, M O; Costeloe, K
Abstract : Complete trisomy 22, with or without mosaicism, has been reported as a distinct syndrome. In this report an infant is described who was externally male but with female rudimentary internal organs and whose karyotype was 47, XX+22.